Mentransformasi Sampah Plastik Menggunakan Teknik Ecobrick Menjadi Spot Foto Aesthetic: Recycle Sampah Plastik untuk Memfasilitasi Era-instagenic - Hikamah, Siti Roudlotul; Syafiqoh, Alya; Firdausi, Jannatul; Ulya, Siti Kumil Laila Hidayatul; Wulandari, Dewi Innayah (LPPM Universitas PGRI Argopuro Jember, 2025)
Waste is a material that cannot be reused and has no utility value. This service aims to prevent the accumulation of waste that can cause environmental pollution, uncleanliness and unhealthy in the campus area. One alternative solution to the waste problem is to use the ecobrick technique. This service method uses Participatory Action Research (PAR), through to know, to understand, to plan, to action, to reflection (5T). The results of this service activity are transforming plastic waste using the ecobrick technique into an aesthetic photo spot through recycling plastic waste to facilitate the instagenic era for students who like to update stories on social media such as TikTok, Instagram (IG), and other popular social media. Therefore, the transformation service activity regarding waste that is changed using the ecobrick technique is very beneficial in various segments, students who like to take photos, the beauty of the environment, and can provide a solution to the accumulation of inorganic waste.